Adivasi Resistance in Early Colonial India : Comprising the Chuar Rebellion of 1799 by J.C. Price and Relevant Midnapore District Collectorate Records - Bhattacharyya, Ananda, (Brill | Manohar Publishers & Distributors, 2017)
In the present compilation the text of Chuar Rebellion written by J.C. Price has been reproduced from the West Bengal District Census Handbook, Midnapore (1951) and the accompanying contemporary official documents have been collected from the Midnapore District Collectorate. The volume focuses on the beginning of the tribal-led peasant resistance in South-West Bengal. Though the year A.D. 1799 is marked in the annals of Midnapore as the year of the great Chuar Rebellion but their resistance began much earlier, right since the Company's accession in Bengal. The grievances of the Adivasis coincided with the precarious condition of the Zamindars leading to the spark of a popular revolt which is commonly known as Chuar rebellion. This volume illuminates with much vigour one of the earliest known instances of subaltern struggle in colonial South Asia.